2021
DOI: 10.3390/ijerph18157995
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Traffic-Related Air Pollution (TRAP) in Primary Schools and Residential Proximity to Traffic Sources on Histone H3 Level in Selected Malaysian Children

Abstract: This study aimed to investigate the association between traffic-related air pollution (TRAP) exposure and histone H3 modification among school children in high-traffic (HT) and low-traffic (LT) areas in Malaysia. Respondents’ background information and personal exposure to traffic sources were obtained from questionnaires distributed to randomly selected school children. Real-time monitoring instruments were used for 6-h measurements of PM10, PM2.5, PM1, NO2, SO2, O3, CO, and total volatile organic compounds (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Particulate matter (PM) is considered one of the most harmful components of ambient pollutants to humans [ 3 ]. Recent studies in the city of Kuala Lumpur, Malaysia demonstrated that PM pollution in this area is greatly contributed by vehicle emissions [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particulate matter (PM) is considered one of the most harmful components of ambient pollutants to humans [ 3 ]. Recent studies in the city of Kuala Lumpur, Malaysia demonstrated that PM pollution in this area is greatly contributed by vehicle emissions [ 4 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, PM potentially modifies histones with consequent alteration of cardiac structures. For example, previous clinical studies have shown that PM exposure induces histone 3 trimethylation (H3K4me3) in neonates, increased circulating levels of histone 3 (H3) in school-age children, and H3 trimethylation (H3K9me3, H3K27me3 and H3K36me3) and acetylation (H3K9ac) in adults ( Zheng et al, 2017 ; Vrijens et al, 2020 ; Suhaimi et al, 2021 ). Remarkably, some of these histone modifications are also associated with CVD.…”
Section: Pm-induced Dna and Histone Modifications Within The Context ...mentioning
confidence: 99%
“…Also, information on respiratory symptoms was gathered by using a questionnaire, which was adapted from American Thoracic Society "ATS-DLD-78". The standardized questionnaire has been translated and proved to be valid in previous studies (22,23). In this study, we focused on four distinct respiratory symptoms that were treated as outcome variables: cough, phlegm, and wheeze for the last 3 months as well as chest tightness for the last 3 years.…”
Section: Assessment Of Respiratory Symptomsmentioning
confidence: 99%